Does early separation of the neonate impact the knowledge, attitudes and feeding practices of their mothers? - A cross sectional study in a rural teaching hospital in Telangana (Panacea Journal of Medical Sciences, 2022)
Introduction: Promotion of knowledge on breast feeding improves the attitude and breast feeding practices of mothers. Studies regarding knowledge, attitude and practices of breastfeeding among Indian mothers are limited, with no studies among mothers of neonates admitted to NICU. Hence this study was planned.Objectives: 1): To assess the difference in knowledge, attitude and practices regarding breast feeding between mothers whose neonates were admitted in NICU ?24 hours of birth, and whose neonates were admitted ?96 hours of birth. 2): To assess gap in knowledge to feeding practices among both groups.Study Design : A Cross Sectional KAP (Knowledge, Attitude and Practice) study.Materials and Methods : 440 postnatal mothers of neonates admitted to NICU between 1June 2019 to 31 December 2020 were included. Based on age at admission of their neonates to NICU, mothers were divided into 2 groups. 1group comprised of 205 mothers of neonates admitted to NICU ?24 hours of life and 2group comprised of 235 mothers of neonates admitted ?96 hours of life. Data was collected from mothers on KAP of breast feeding by interview, on a pretested questionnaire by the primary researcher.Results : The group 2 mothers whose neonates were admitted at ?96 hours of life demonstrated better KAP which was statistically significant. There was no significant difference noted in implementation of knowledge to practices among all 440 mothers. Out of 440 mothers, only 17% had knowledge to initiate breast feeds within 1hour after birth & 15% fed the babies within 1hour after birth. 88% of mothers had knowledge that colostrum should be fed & 82 % practiced it; 80% knew that pre-lacteals should be avoided & 87% practiced it; 68% were aware of burping the baby; 91% practiced burping before putting the baby down.Conclusions: Early separation of neonates from mothers impacts the knowledge, attitude and practices towards breastfeeding. Poor attendance at the antenatal counselling clinic is also a contributing factor.